Mapeando a aprendizagem profissional por meio da análise institucional - Cruzoletto, João Vitor (2012)
The proposed study aims to problematize the discussion about the Professional Leaning Policy, particularly its educational process of training/formatting technical professional of the individual-citizen-worker young for the world of work. The scientific text is service begins by analyzing the relationship between the Professional Learning Institution versus the Professional Education Institution, in an attempt to determine how and Where it materializes and structure nationally the Professional Learning, as well as to demonstrate the technical and institutional arrangements used to evaluate, finance and maintain the leaning programs/projects. Following on national data were presented who seek to give the Professional Leaning a status of "intersectoral policy" social impact on Brazilian society. Finally, the research is devoted to analysis of a program/project professional social learning developed by a Socioeducative Care Entity headquartered in Maringá - Paraná. Methodologically, the techniques used consisted of memories of the Worker/researcher and documentary research conducted in the archives-dead of the collective teenagers who were in the process of Learning in the period 2007-2009, formally authorized by the responsible authority. Participant observation was used to analyze the institutional democratic spaces that today this social establishment is inserted to discuss the Apprenticeship.